Consumer engagement behavior perspective in social media: Mediating role and impact on brand equity - Zailskaite-Jakste, Ligita; Minelgaite, Inga (Journal of Eastern European and Central Asian Research (JEECAR), 2021)
This study analyzes marketing communication (MC) impact on brand equity (BE) in social media (SM) seeking to identify mediating role of consumer engagement behavior (CEB) between generated functional and hedonic content on brand equity (BE). The CEB is divided into three levels: consuming, contributing, and creating. A survey-based empirical study with 402 respondents was conducted in the Eastern Europe country Lithuania. The implemented five control variables disclosed new mediation tracks and the good fit of the model, with the main findings of the research being that CEB occurring via SM platforms mediates the relationship between marketing communication and BE. These outcomes suggest that companies seeking to make an impact on BE through CEB in level creation, should develop company-created utilitarian content which may engage consumers, extending the reach of their content and helping to facilitate long-term brand loyalty. Keywords: marketing communication; consumer engagement behavior; social media; brand equity.